Darwin's dice : the idea of chance in the thought of Charles Darwin - Johnson, Curtis N., 1948- (Oxford University Press, 2015)
For evolutionary biologists, the concept of chance has always played a significant role in the formation of evolutionary theory. As far back as Greek antiquity, chance and ""luck"" were understood to be key factors in the evolution of the natural world. Emphasizing chance is an entire way of thinking about nature, and it is also one of the key ideas that separates Charles Darwin from other systematic biologists of his time. Studying the concept of chance in Darwin's writing reveals core ideas in his theory of evolution, as well as his reflections on design, purpose, and randomness in nature's.